2016
DOI: 10.1016/j.jdiacomp.2016.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypertension and chronic hypertension on the risk of diabetes among gestational diabetes women

Abstract: Aims We aimed to examine the association of gestational hypertension and chronic hypertension at the inter-conception examination with Type 2 diabetes risk among women with a history of gestational diabetes. Methods We conducted a population-based study among 1261 women who had a history of gestational diabetes at 1–5 years after delivery in Tianjin, China. Logistic regression or Cox regression was used to assess the associations of gestational hypertension and chronic hypertension at the inter-conception ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Finding similar to above study was also found in present study where GDM was statistically associated with weight and BMI during gestation, but no significance was found between family history as in rural areas, most of diabetic cases are under diagnosed. Gestational diabetes is associated with pregnancy induced hypertension in studies conducted by Bryson et al, Yaun et al and Parveen et al [11][12][13] In present study it was seen that mean systolic blood pressure and mean diastolic blood pressure was more in mothers with gestational diabetes than those without GDM.…”
Section: Discussionsupporting
confidence: 54%
“…Finding similar to above study was also found in present study where GDM was statistically associated with weight and BMI during gestation, but no significance was found between family history as in rural areas, most of diabetic cases are under diagnosed. Gestational diabetes is associated with pregnancy induced hypertension in studies conducted by Bryson et al, Yaun et al and Parveen et al [11][12][13] In present study it was seen that mean systolic blood pressure and mean diastolic blood pressure was more in mothers with gestational diabetes than those without GDM.…”
Section: Discussionsupporting
confidence: 54%
“…The women in our study with undiagnosed type 2 diabetes were just as likely to have a primary care physician and also had more visits to their primary care physician prior to pregnancy then those with GDM alone, and therefore this represents missed opportunities for a diabetes diagnosis pre-pregnancy. Also, many of them had chronic hypertension, which should alert caregivers to the increased risk of diabetes [22]. People of a lower socioeconomic status frequently experience a delay in their diabetes diagnosis and receive a lower level of care [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the self-administered questionnaire, women who reported doctors-diagnosed hypertension after 20 gestational weeks, including gestational hypertension, preeclampsia, severe preeclampsia or eclampsia, were classified as having a history of HDP (ref. 21 ).…”
Section: Methodsmentioning
confidence: 99%